Cigarette smoke extract (CSE) induces RAGE-mediated inflammation in the Ca9-22 gingival carcinoma epithelial cell line. (August 2017) - Sanders, Nolan T.; Dutson, Derek J.; Durrant, Justin W.; Lewis, Joshua B.; Wilcox, Shalene H.; Winden, Duane R.; Arroyo, Juan A.; Bikman, Benjamin T.; Reynolds, Paul R.
Highlights: Tobacco smoke induces RAGE expression by gingival epithelial cells. RAGE-mediated inflammation follows tobacco smoke exposure. Semi-s ynthetic glycosa minog lycane thers (SAGEs) attenuate inflammation. Abstract: Objective: The oral environment is anatomically positioned as a significant gateway for exposure to environmental toxicants. Cigarette smoke exposure compromises oral health by orchestrating inflammation. The receptor for advanced glycation end-products (RAGE) has been implicated in smoke-induced inflammatory effects; however, its role in the oral cavity is unknown. The purpose of this study was to determine RAGE expression by immortalized gingival carcinoma cells and the degree to which RAGE-mediated signaling influences inflammation. Design: Gingival epithelia cells (Ca9-22) were exposed to 10% cigarette smoke extract (CSE) for six hours and screened for RAGE expression and inflammatory mediators. Results: Quantitative PCR and immunoblotting revealed increased RAGE expression following exposure. Furthermore, exposure activated RAGE signaling intermediates including Ras and NF-κB. IL-6 and IL-1β were also elevated in cell culture medium from CSE-exposed cells when compared to controls. A family of anionic, partially lipophilic sulfated polysaccharide derivatives known as semi-s ynthetic glycosa minog lycane thers (SAGEs) were used in an effort to block RAGE signaling. Co-treatment of CSE and SAGEs ameliorated inflammatory responses. Conclusions: These results provide a new perspective on a mechanism of cigarette smoke induced oral inflammation. Further work may show RAGE signaling as a potential target in the treatment of diseases of the oral cavity exacerbated by tobacco smoke exposure.